The Impact of Education on Patriarch Culture and Gender Equality - Benedikta Yosefina Kebingin; Armada Riyanto (Journal of Asian Orientation in Theology, 2022)
This article will explore the independence that is actually expected by every human being, both women and men in the framework of education under the title, "Impact of Education on Patriarchal As This article would analyze on the true independence that expected  by every human  both of women and men in frame  of Education with the title , “The Impact of Education on Patriarchate  Culture and Gender Equality". In this sense, education must be placed in the perspective of liberation. Education is for all and lasts for life. Patriarchate refers to a system of legitimate relations in the fields of law, economy and politics and strengthens domination relations in a society. The research takes place in the mainland area of East Flores with characteristic of a strong patriarchate culture. Observations were made on the family in the interaction of husband and wife dealing with work and tasks in the realm they carried so that the authors were sent to find out whether there is an influence of education on patriarchate culture and therefore patriarchate culture affects gender equality which has an impact on women's participation. The methodology used in this study is interpretive, with a qualitative model and a phenomenological approach. The data collection technique is done through interviews. This study found that patriarchate culture, gender equality and the  involvement of East Flores women that were influenced by the higher education received by the community. Thus, this study is different from the one conducted by Shannon McAlister with the title, “Christ as the Woman Seeking Her Lost Coin: Luke 15:8-10 and Divine Sophia in the Latin West” in the Journal of “Theological Studies”, 2018, Vol. 79, no. 1, pp 7-35